2019
DOI: 10.3926/jiem.2885
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive insight into Lean management: Literature review and trends

Abstract: Purpose: Lean Management has evolved into an inter-disciplinary subject with linkages to Operations Management, Organizational Behaviour, and Strategic Management. The objective of this paper is to review journal articles on lean published in major academic sources with a view to  provide taxonomy of the field of lean management facilitating identification of the pertinent themes that exists in literature, while presenting an overview of the main definitions, chronological evolution, diffusion among developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Most scientific research on lean management has a qualitative and interpretative approach (Pearce and Pons, 2019), in which case study is the preferred method (Pearce and Pons, 2019;Sinha and Matharu, 2019). In this field, this study introduces a discussion of lean management in the administrative areas, based on the theoretical framework of information management.…”
Section: Introductionmentioning
confidence: 99%
“…Most scientific research on lean management has a qualitative and interpretative approach (Pearce and Pons, 2019), in which case study is the preferred method (Pearce and Pons, 2019;Sinha and Matharu, 2019). In this field, this study introduces a discussion of lean management in the administrative areas, based on the theoretical framework of information management.…”
Section: Introductionmentioning
confidence: 99%
“…The lean principle and digital transformation can be applied in tandem to deliver innovation (Sanders, Elangeswaran & Wulfsberg, 2016). The Internet of Think (IoT) enables the disrupting and revolutionizing of the lean principle rendering it relevant to current business trends (Sinha & Matharu, 2019). Integrated IT management is crucial since it enables the PSC to ensure product availability, provide a more rapid customer service and enhance both inventory control and product visibility (Guimarães et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another literature review was completed by Ciccullo et al (2018) who studied 73 academic papers which addressed the integration of lean, agile and sustainable supply chain management paradigm. A recent work contributed by Sinha and Matharu (2019) reviewed 447 research articles drawn from 51 academic journals. They indicated that the interest in the lean principle has gained momentum over the past few years due to global competition and increasing operational costs.…”
Section: Lean Supply Chainmentioning
confidence: 99%
“…Ukrainian business is actively transforming, increasing its competitiveness in world markets and creating a new internal institutional environment that encourages all domestic companies to change more dynamically in accordance with market requirements. Lean-management is the organizational philosophy that will allow the company to improve quality, be more flexible and economical and adapt more quickly to new trends [1].…”
Section: Currentlymentioning
confidence: 99%